Crystal structure of 5-(4-methoxyphenyl)- 3-(4-methylphenyl)-4,5-dihydro-1Hpyrazole- 1-carbaldehyde - Adam, Farook; Samshuddin, Seranthimata; Shruthi, Shruthi; Narayana, Badiadka; Ameram, Nadiah (International Union of Crystallography, 2015)
In the title compound, C18H18N2O2, the pyrazole ring has a twisted conformation on the CH—CH2 bond. The tolyl ring and the 4-methoxyphenyl ring are inclined to the mean plane of the pyrazole ring by 4.40 (9) and 86.22 (9), respectively, while the two aromatic rings are inclined to one another by 88.75 (9). In the crystal, molecules are linked via bifurcated C—H (O,O) hydrogen bonds and C—H interactions, forming sheets lying parallel to the ab plane.